High-efficiency generation of induced pluripotent mesenchymal stem cells from human dermal fibroblasts using recombinant proteins. Issue 1 (December 2016) - Chen, Fanfan; Zhang, Guoqiang; Yu, Ling; Feng, Yanye; Li, Xianghui; Zhang, Zhijun; Wang, Yongting; Sun, Dapeng; Pradhan, Sriharsa
Abstract Background Induced pluripotent mesenchymal stem cells (iPMSCs) are novel candidates for drug screening, regenerative medicine, and cell therapy. However, introduction of transcription factor encoding genes for induced pluripotent stem cell (iPSC) generation which could be used to generate mesenchymal stem cells is accompanied by the risk of insertional mutations in the target cell genome. Methods We demonstrate a novel method using an inactivated viral particle to package and deliver four purified recombinant Yamanaka transcription factors (Sox2, Oct4, Klf4, and c-Myc) resulting in reprogramming of human primary fibroblasts. Whole genome bisulfite sequencing was used to analyze genome-wide CpG methylation of human iPMSCs. Western blot, quantitative PCR, immunofluorescence, and in-vitro differentiation were used to assess the pluripotency of iPMSCs. Results The resulting reprogrammed fibroblasts show high-level expression of stem cell markers. The human fibroblast-derived iPMSC genome showed gains in DNA methylation in low to medium methylated regions and concurrent loss of methylation in previously hypermethylated regions. Most of the differentially methylated regions are close to transcription start sites and many of these genes are pluripotent pathway associated. We found that DNA methylation of these genes is regulated by the four iPSC transcription factors, which functions as an epigenetic switch during somatic reprogramming as reported previously. These iPMSCs successfully differentiate into three embryonic germ layer cells, both in vitro and in vivo. Following multipotency induction in our study, the delivered transcription factors were degraded, leading to an improved efficiency of subsequent programmed differentiation. Conclusion Recombinant transcription factor based reprogramming and derivatization of iPMSC offers a novel high-efficiency approach for regenerative medicine from patient-derived cells.